St. Gallen/Vienna 2021: A Brief Summary of the Consensus Discussion on Customizing Therapies for Women with Early Breast Cancer - Thomssen, Christoph (Breast Care (Basel), 2021)
Because of the COVID-19 pandemic, the 2021 St. Gallen/Vienna Consensus Conference on Early Breast Cancer Treatment Standards had to be held virtually. Despite the challenge of convening global contributors to both the conference itself as well as the important Consensus Panel, the scientific committee and the organizers managed to organize a well-received scientific conference, and also the panel discussion was well received in the worldwide scientific community, as indicated by numerous positive feedbacks already within the first 24 h. The virtual format was unusual, but opened the door for new elements such as Consensus questions proposed from the audience, but also live audience interaction on both days − the Consensus was split into 2 parts in order to accommodate as many time zones globally as possible, leading to almost a doubling of discussion time compared to previous meetings. Also, about 3,400 participants from over 100 countries and all continents came together, including many colleagues who could attend for the first time from world regions with restrictions that so far did not allow the travel to Vienna. Traditionally, the Panel votings and discussions were preceded by 3 days of high-level live-discussions about the lectures that were available on demand already a week before. Also, all the lectures and live discussions in mini-panels are made available online for at least 6 months (https://www.oncoconferences.ch/events/bcc-2021/). The traditional panel votings were once more moderated by Eric Winer from Harvard and included interactive elements such as audience votings and audience questions, presented by Michael Gnant. This rapid report by the editors-in-chief of Breast Care summarizes the results of the 2021 international panel votings with respect to locoregional and systemic treatment as a quick news update for our readers and clearly does not intend to replace the official St. Gallen Consensus publication that will follow shortly in Annals of Oncology.